A review on the role of thermogravimetric analysis in assessing thermal stability and degradation of wood - Charles Michael Albert; Kang Chiang Liew (Springer, 2025)
This article provides an in-depth review of thermogravimetric analysis, highlighting the principle of pyrolysis and the analytical technique, as well as their significance for wood’s thermal degradation kinetics. The influence of the operating conditions and the material parameters on the thermal decomposition behavior has also been discussed. Besides that, the comparative analysis of different treatments and operating conditions applied across various wood species has been thoroughly reviewed, where treatments such as torrefaction improved its thermal stability. Moreover, different approaches to improving wood’s thermal stability and their effects on the thermogravimetric analysis have been critically reviewed, and the mass loss, onset temperature, and char yield during the experiment show notable changes. This com- prehensive review aims to provide insights into the important role of this analytical technique in assisting researchers and practitioners in selecting appropriate treatments to improve wood’s properties for safer and more sustainable use in a wide range of applications.